A case study on the factor of marketing effectiveness at Amanah Raya Berhad Malaysia / Ammar Amierul Zahba - Zahba, Ammar Amierul (Faculty of Business and Management, 2009)
Amanah Raya Berhad or ARB are known as Malaysia’s premier trustee organization. This organization have served towards our Malaysian people for over 80 years since its establishment as the Department of Public Trustees and Official Administrators on 1 May 1921 and play their role as the market leader in providing trust, legacy management and also Will- services.